Esomeprazole Treatment of Frequent Heartburn: Two Randomized, Double-Blind, Placebo-Controlled Trials. Issue 4 (July 2014) - Peura, David A.; Traxler, Barry; Kocun, Christopher; Lind, Tore
Abstract: Purpose: To determine the efficacy of a 14-day regimen of esomeprazole 20 mg for the treatment of frequent heartburn in subjects who are likely to self-treat with over-the-counter medications without consulting a health care provider.Methods: Adults with frequent heartburn ≥ 2 days per week in the past 4 weeks were randomly assigned to 14-day double-blind treatment with esomeprazole 20 mg once daily or placebo in 2 identical multicenter studies (ClinicalTrials.gov identifiers: NCT01370525, NCT01370538). The primary efficacy outcome was percentage of heartburn-free 24-hour days across 14 days. Secondary efficacy outcomes included heartburn resolution, defined as heartburn ≤ 2 days over 14 days, and percentages of subjects reporting ≤ 1 day with heartburn in the first and final weeks of treatment. Subjects recorded data in daily self-assessment diaries.Results: The percentage of heartburn-free 24-hour days over 14 days was significantly higher ( P < 0.0001) in subjects receiving esomeprazole 20 mg compared with placebo in study 1 (N = 331; 46.13% vs 33.07%, respectively) and study 2 (N = 320; 48.00% vs 32.75%, respectively). Significantly more subjects treated with esomeprazole 20 mg had heartburn resolution over 14 days and in the first and final weeks compared with placebo. Within the first 4 days, the proportion of subjects with heartburn-free days was significantly greater with esomeprazole 20 mg versus placebo. Treatment was generally well tolerated, with a safety pattern consistent with the known profile for esomeprazole.Conclusion: A 14-day regimen of esomeprazole 20 mg once daily was effective for treating frequent heartburn in subjects who are likely to self-treat with over-the-counter medications.